Empowering Communities from Below - Kusumadewi, Afina Putri (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2024)
Community organising, as a form of bottom-up development, challenges top-down approaches that traditionally view communities as passive recipient rather than active agents of change. This study examines the internal dynamics of women farmers group (kelompok wanita tani/KWT) Lestari in Pakembinangun, Sleman, under the leadership of Sri Hartanti, a key figure who has been instrumental in the group’s development. Using a qualitative method through in-dept interview, the research identifies the organisational model applied by KWT Lestari through twelve analytical indicators, including goals of community action, assumptions concerning community structure and problem conditions, basic change strategies, characteristic change tactics and techniques, salient practitioner roles, medium of change, orientation toward power structures, boundaries of the community client system, assumptions regarding sub-community interests, conceptions of public interest, client population, and client role, Despite challenges in sustaining member participation, findings show that KWT Lestari effectively employs the locality development model, positioning members as active change agents within their community. This study contributes to understanding how community organising can succeed in diverse social, cultural, and economic contexts, offering insights for future community-based development efforts.